A simple and robust method for radiochemical separation of no-carrier-added 64Cu produced in a research reactor for radiopharmaceutical preparation. (November 2020) - Chakravarty, Rubel; Rajeswari, Ardhi; Shetty, Priyalata; Jagadeesan, K.C.; Ram, Ramu; Jadhav, Sachin; Sarma, Haladhar Dev; Dash, Ashutosh; Chakraborty, Sudipta
Abstract: Copper-64 is an excellent theranostic radiometal that is gaining renewed attention of the clinical community in the recent times. In order to meet the increasing demand of this radiometal, we have demonstrated the viability of its production via 64 Zn (n, p) 64 Cu reaction in a nuclear reactor. A semi-automated radiochemical separation module based on selective extraction of 64 Cu as dithizonate complex was developed. The maximum available activity at the end of irradiation was 700 MBq. The overall yield of 64 Cu after the separation process was >85% and it could be obtained with 12 GBq/μg specific activity, >99.9% radionuclidic purity and >98% radiochemical purity. The separated 64 Cu could be utilized for preparation of a wide variety of radiopharmaceuticals. Highlights: Copper-64 was produced via 64 Zn (n, p) 64 Cu reaction in a research reactor. A procedure was developed for separation of 64 Cu from the irradiated target. The separated 64 Cu was found suitable for preparation of radiopharmaceuticals.